PERKEMBANGAN MATERI GENETIKA PADA PENGAJARAN BIOLOGI DI SMU - Suratsih Suratsih (Jurnal Cakrawala Pendidikan, 1999)
In order to suit and respond to the develop-=ment of science and technology and other relatedissues, a curriculum replacement is a necessity.This curriculum analysis was carried out inorder to observe the development of genetics subjectmatter in the curriculum of 1984 into that of1994 and the relevance of these curricula to the anticipationof recent and future developments. Geneticswas studied equally well. Analysis was conductedby comparing the curriculum of 1984 to that of 1994and considering the development of recent and futuregenetics.The result shows that the genetics subject matterof the curriculum of 1984 has not shown any change;however, biotechnology as applied genetics is added tothe curriculum of 1994. In conclusion, the genetics subjectmatter of the curriculum of 1984 is still not adequateto anticipate the development of recent and hturegenetics. Addition of some related subject mattershould be proposed, covering genes and gene expression,chromosomes (structure, variation of structure,variation of chromosome numbers) and cytoplasm inheritance.